(untitled) (Cambridge, UK, 2004)
Adaptive speciation occurs when biological interactions induce disruptive selection and the evolution of assortative mating, thus triggering the splitting of lineages. Internationally recognized authorities explain exciting developments in modeling speciation, including celebrated examples of rapid speciation by natural selection. The text is geared toward students and researchers in biology, physics, and mathematics.
Keywords: Adaptation ( biology ),Species